Perspektif Mahasiswa Matematika tentang Pencampuran Ekstrak Lidah Buaya (Aloe Vera) dengan Larutan Asam Lemah terhadap Kesehatan dan Kelembutan Rambut - Dimas Ridho; Tita Juwitaningsih; Syifani Azzura; Annisa Saktiono; Agnia Kamila Rambe; Jona Mikhael Hutagaol; Lutfiah Syahrawani Siregar (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to analyze the perspectives of mathematics students on mixing aloe vera extract with weak acid solution for hair health and softness. The research method used is descriptive quantitative through the distribution of questionnaires to 43 mathematics students at Medan State University and other universities in North Sumatra. The questionnaire consists of 19 statements covering aspects of knowledge (12 items), environmental awareness (4 items), and psychomotor (4 items) with a Likert scale of 1-5. The results showed that the majority of respondents had good knowledge about the benefits of aloe vera for hair care (mean = 4.02), but the understanding of weak acid solution and its mechanism of action was still moderate (mean = 3.12). The environmental awareness aspect showed a high value (mean = 3.76) which reflects the tendency of students to choose natural products. Meanwhile, the psychomotor aspect showed a moderate value (mean = 3.44), which indicates the limitations of respondents' skills in applying hair care products optimally. This study found a positive correlation between knowledge about natural ingredients and the tendency to use natural-based products for hair care. The results of this study are expected to be the basis for developing hair care product formulations based on natural ingredients that suit the needs and preferences of students.